Study on improving yield and antioxidant enzyme activities in millet by rationing molybdenum and nitrogen - Yuan Zhao; Guoliang Wang; Min Liu; HongTao Xue; PeiYue Zhao; BaiShu Han; HuiPing Fan; Rui Wang; LiXia Wang; ErHu Guo; AiYing Zhang; AiYing Zhang (Frontiers in Plant Science)
The application of appropriate nitrogen and molybdenum fertilizer can improve the growth and development of plants, increase photosynthetic efficiency, regulate active oxygen metabolism in vivo, maintain the oxidation balance required for normal cell growth, enhance the activity of crop antioxidant enzymes and dry matter accumulation, so as to increase crop yield. In order to investigate the effect mechanism of nitrogen fertilizer combined with foliar molybdenum fertilizer on millet yield and antioxidant enzyme activity, two nitrogen application gradients (N0 (0 kg/hm2) and N1 (75 kg/hm2) were set with millet variety Changnong 47 as material. Leaf molybdenum fertilizer Mo0 (0 %), Mo1 (0.1 %), Mo2 (0.2 %), Mo3 (0.3 %) and Mo4 (0.4 %) were sprayed at the joining stage. Photosynthetic parameters, chlorophyll content, antioxidant enzyme activity, dry matter accumulation and yield at the complete ripening stage were measured. After the analysis of significant difference, the results showed that the combined application of molybdenum nitrogen significantly increased the yield of millet, and the maximum yield under the Mo3 treatment was 5869.04 kg/hm2 under the N1 condition, which was 13% higher than that under the no fertilization treatment. The total dry matter accumulation was 36.96 g/ plant, which was 31% higher than that without fertilization. The net photosynthetic rate (Pn) and stomatal conductivity (gs) increased first and then decreased with the increase of molybdenum fertilizer concentration gradient, and reached the maximum values under N1Mo3 condition, which were 24.77 μmol•m-2•s-1 and 391.33 mol•m-2•s-1, respectively. Application of molybdenum fertilizer can improve the activities of superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) in the test samples. In conclusion, under N1 condition, Mo3 (0.3%) treatment can effectively improve millet yield, photosynthetic characteristics and antioxidant enzyme activity. The results of this study provided theoretical basis and data support for the application of nitrogen and molybdenum fertilizer in millet production.